2016
DOI: 10.1158/1940-6207.capr-15-0257
|View full text |Cite
|
Sign up to set email alerts
|

Unconjugated Bilirubin Is a Novel Prognostic Biomarker for Nasopharyngeal Carcinoma and Inhibits Its Metastasis via Antioxidation Activity

Abstract: Distant metastasis is the most common cause of treatment failure and mortality in nasopharyngeal carcinoma (NPC) patients. Thus, it is important to understand the mechanism of NPC metastasis and identify reliable prognostic factors. In this study, we investigated the prognostic value of unconjugated bilirubin (UCB), which was previously considered a byproduct of heme catabolism, in NPC patients and examined the effects of UCB on NPC metastasis. The receiver operating characteristic analysis-generated UCB cutof… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…At the same time, a previous study on nasopharyngeal carcinoma (NPC) showed that IBI could inhibit NPC metastasis by inhibiting reactive oxygen species (ROS) production, and acted as a favorable prognostic factor. 11 What's more, IBI was also reported to be an independent prognostic factor in NSCLC. 13 On the other hand, it was reported that IBI could induce cell apoptosis in colon cancer cell lines by triggering mitochondrial depolarization, 17 suggesting that elevated IBI level could predict good outcome.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, a previous study on nasopharyngeal carcinoma (NPC) showed that IBI could inhibit NPC metastasis by inhibiting reactive oxygen species (ROS) production, and acted as a favorable prognostic factor. 11 What's more, IBI was also reported to be an independent prognostic factor in NSCLC. 13 On the other hand, it was reported that IBI could induce cell apoptosis in colon cancer cell lines by triggering mitochondrial depolarization, 17 suggesting that elevated IBI level could predict good outcome.…”
Section: Discussionmentioning
confidence: 99%
“…16 However, these cut-off values varied from previous studies (date were listed in Table 3). [11][12][13][14][15] With the aspect to CRC, Gao used the threshold were slightly lower than our cut-off value of DBIL. Number of patients from different tumor stages and different geographic regions may be could explain this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction of apoptosis via activation of caspases is a critical feature associated with the effectiveness of potential cancer treatments [42,43] including the use of tetrapyrrolic bile pigments in human cancer cells [44]. Apart from being used as a novel biomarker for nasopharyngeal carcinoma [45], UCB has the potential to cause cell cycle arrest at G0/G1 and exert pro-oxidant effects at high concentrations [46]. Human biliverdin reductase, which chemically reduces biliverdin to bilirubin, was recently implicated as a regulator in cancer development and maybe useful in designing biomarkers for cancer patients [47].…”
Section: Discussionmentioning
confidence: 99%
“…18,19 However, upon consideration of the inconvenient and expensive detection of UGT1A1, it is speculated that serum bilirubin, which was tested routinely, might be an available prognostic biomarker for CRC. At the same time, serum bilirubin, including total bilirubin (TBIL), direct bilirubin (DBIL), and indirect bilirubin (IBI) have been reported by numerous studies as promising prognostic biomarkers in various cancers, including breast cancer, 20 non-small-cell lung cancer, 21 nasopharyngeal carcinoma, 22 pancreatic adenocarcinoma, and CRC. 23,24 Until now, few studies have reported the prognostic value of serum bilirubin in CRC.…”
Section: Introductionmentioning
confidence: 99%